2009
DOI: 10.1016/j.biomaterials.2008.10.024
|View full text |Cite
|
Sign up to set email alerts
|

The osteogenic differentiation of rat bone marrow stromal cells cultured with dexamethasone-loaded carboxymethylchitosan/poly(amidoamine) dendrimer nanoparticles

Abstract: There is an increasing interest in developing novel macromolecular vehicles for the intracellular and controlled delivery of bioactive molecules, since they can allow modulation of the cellular functions in a more effective manner ex vivo, and maintain the cellular phenotype in vivo upon re-implantation. The present study was designed to investigate the effect of combining novel dexamethasone-loaded carboxymethylchitosan/poly(amidoamine) dendrimer (Dex-loaded CMCht/PAMAM) nanoparticles and, both HA and SPCL sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
102
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(105 citation statements)
references
References 47 publications
2
102
0
Order By: Relevance
“…The increase in DNA content in BM indicated that hMSCs were able to grow in the encapsulating PEGDA matrix but DNA content decreased with incubation time as the encapsulated cells underwent differentiation in OM consistent with previous reports. 52,53 Addition of BMP-2 peptide, peptide hydrophobicity, or peptide conjugation to the PEGDA matrix did not have a significant effect on cell number with incubation time.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in DNA content in BM indicated that hMSCs were able to grow in the encapsulating PEGDA matrix but DNA content decreased with incubation time as the encapsulated cells underwent differentiation in OM consistent with previous reports. 52,53 Addition of BMP-2 peptide, peptide hydrophobicity, or peptide conjugation to the PEGDA matrix did not have a significant effect on cell number with incubation time.…”
Section: Resultsmentioning
confidence: 99%
“…[16][17][18] Our group, as an example, successfully exploited barium titanate NPs (BTNPs; Figure 1A) as a possible agent for the improvement of osteogenic differentiation of MSCs. 19 BTNPs belong to a class of ferroelectric materials showing high piezoelectricity, 20 and with regard to biomedical applications, they demonstrate high cytocompatibility, 21 excellent properties as nonlinear imaging probes, 22 and the ability to deliver doxorubicin in cancer cells by improving Notes: scanning electron microscopy image of BTNPs (A).…”
mentioning
confidence: 99%
“…9,10 The following paragraph focuses on the use of nanoparticles as an effective protein or drug delivery system to support bone tissue regeneration. For this purpose, several nondegradable particles, such as silica, lipid, dendrimer, hydroxyapatite, or gold nanoparticles, [43][44][45][46][47][48][49][50] as well as degradable particles made of poly(L-lactide) 51,52 or poly(L-lactideco-glycolide) (PLGA), 11,42,[52][53][54][55][56] have been used. Frequently, nanoparticles were combined with scaffolds such as proteinaceous hydrogels or degradable polymeric matrixes to facilitate application in bone.…”
Section: Drug Deliverymentioning
confidence: 99%
“…Frequently, nanoparticles were combined with scaffolds such as proteinaceous hydrogels or degradable polymeric matrixes to facilitate application in bone. 47,48,53,55,56 As bone contains bone-forming cells, the osteoblasts, and bone-resorbing cells, the osteoclasts, which act in concert to guarantee bone homeostasis, 57,58 different strategies can be envisioned that could promote the regeneration of bone tissue. On the one hand, osteoblasts could be supported by nanoparticle-based growth factor delivery.…”
Section: Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation